2019
DOI: 10.5758/vsi.2019.35.4.225
|View full text |Cite
|
Sign up to set email alerts
|

Use of Paclitaxel Eluting Stents in Arteriovenous Fistulas: A Pilot Study

Abstract: PurposeWe report short-term patency outcomes of a proof of concept study conducted to determine the efficacy of drug-eluting stent (DES) for the treatment of arteriovenous fistula (AVF) stenosis in hemodialysis patients.Materials and MethodsThis is a single-center, retrospective observational study involving 10 patients with AVF dysfunction treated with DESs between January 2017 and December 2017. The primary outcome was AVF patency confirmed by sonographic and clinical assessment at 1 month and 6 to 9 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
1
5
2
Order By: Relevance
“…This effect causes inhibition of smooth muscle cell proliferation and migration, resulting in reduction of neointimal hyperplasia. 16,17 No obvious neointimal hyperplasia ingrowth was found into DES in all patients that had 6-and 12-month follow-up angiogram that corresponding with the study of Dinh et al 13 that showed no significant neointimal hyperplasia at 6 months follow up by duplex ultrasound. The primary patency of DES at target lesion in this study was high; however, the primary patency rate of circuit was not significantly different before and after DES placements.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…This effect causes inhibition of smooth muscle cell proliferation and migration, resulting in reduction of neointimal hyperplasia. 16,17 No obvious neointimal hyperplasia ingrowth was found into DES in all patients that had 6-and 12-month follow-up angiogram that corresponding with the study of Dinh et al 13 that showed no significant neointimal hyperplasia at 6 months follow up by duplex ultrasound. The primary patency of DES at target lesion in this study was high; however, the primary patency rate of circuit was not significantly different before and after DES placements.…”
Section: Discussionsupporting
confidence: 71%
“…This study showed high primary patency rate of stent placement at target lesions 100% and 86% at 6 and 12 months, respectively, and significantly increased patency rate comparing with before stenting at target lesions. Our result showed a better primary patency of DES placement at the target lesion than a pilot study by Dinh et al, 13 which used DES in AVF, with result of 77.8% in 6-month primary patency of DES. However, the most common dialysis access in our study was AVG, whereas the study by Dinh et al 13 | 167 in dialysis access can provide mechanical support in the significant elastic recoil stenosis.…”
Section: Discussioncontrasting
confidence: 41%
See 2 more Smart Citations
“…[ 9 ] To solve this problem, various interventional procedures, such as using drug-eluting balloons or stents, for reducing AV fistula stenosis are being performed; medical treatment for preventing stenosis and obstruction is also being considered. [ 17 19 ]…”
Section: Discussionmentioning
confidence: 99%